Physical and chemical properties of disinfectant preparation of «DZPT-2» - Палій, А. П.; Завгородній, А. І.; Дегтярьов, І. М. (Scientific Progress & Innovations, 2012)
In the article are presented results of determination of physical and chemical properties of new disinfectant preparation of «DZPT-2». It is established disinfectant preparation has a less surface-tension than water and shows insignificant corrosive activity standard steel ST3, stainless steel X25T, galvanized sheet steel, aluminium AD1M, duralumin D1, brass L80, copper M1 by comparison to a preparation-standard (3 % alkaline solution of formaldehyde) and can be used for the sanitization of metallic constructions and equipment of stock houses.